Pengaruh penggunaan ICT terhadap hasil belajar aqidah akhlak di MI Muhammadiyah Walen 1 Simo Boyolali - Mulyoto Mulyoto; Mujiburrohman Mujiburrohman; Meti Fatimah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The aims of this study were: 1) To determine the effect analysis of the experiential learning method on the ability and willingness to learn in students and the learning experiences of students at MIM Walen Simo Boyolali; 2) To find out the analysis of the influence of the use of ICT on learning achievement in Aqeedah Akhlak lessons at MIM Walen Simo Boyolali; 3) To find out the effect analysis of the experiential learning method and the use of ICT on the learning achievement of aqeedah morals at MIM Walen Simo Boyolali. This research method uses quantitative with regression analysis and hypothesis taking. The results of the research are data analysis used to analyze multiple linear regression, the results of the equation Y = 12.808 + 0.200 X1 + 0.097 X2 are obtained. The results of hypothesis testing I show that the results of data analysis show the value of tcount (2.695) > ttable (2.010), then the research hypothesis I is accepted. The results of hypothesis testing II show that the results of data analysis show the value of tcount (2.579) > ttable (2.010), then the research hypothesis II is accepted. The results of testing the third hypothesis of the study show that the value of Fcount (3.954) > Ftable (3.19), so that the research statement of hypothesis III is accepted, then the third hypothesis shows that the experiential learning method, and the use of ICT significantly and simultaneously affect learning achievement in aqidah lessons morals at MIM Walen Simo Boyolali. The value of the coefficient of determination (adjusted R Square) is 0.152 or 15.2%. This value can be interpreted that the independent variable in this case the experiential learning method and the culture of using ICT can increase the dependent variable (learning achievement in aqidah morals lessons) by 15.2% while the remaining is 84.8% (100% -15.2%), influenced by other variables not examined, for example the ability and willingness to learn in students and the learning experience of students.